L2 learning challenges and needs of university students: a preliminary study - Mohd Shah, Parilah; Hashim, Nor Haslinda; Yusof, Aminuddin; Din, Rosseni; Abdul Karim, Aidah; Abd Rahman, Ghazaliyusri (Elsevier, 2013)
Technology demands individuals to be knowledgeable in another language, in particular the English language. Learning a second language (L2) is one of the significant experiences encountered by a student in an institution of higher learning. Some L2 acquirers would be more successful than others in acquiring another language. University students need a good knowledge of the English language to access the globalized world technologically. An investigation was conducted to examine the challenges, needs, attitudes and beliefs about English language learning held by university students in Malaysia. The subjects exhibited somewhat differing responses with respect to L2 learning perceptions of experiences. The paper also addressed the practical implications of the results.